Approximation and interpolation of entire functions of several complex variables on arbitrary compact sets / G. S. Srivastava and Susheel Kumar - Srivastava, G. S.; Kumar, Susheel (Universiti Teknologi MARA, Negeri Sembilan, 2012)
In the present paper, we study the polynomial approximation of entire functions of several complex variables. The characterizations of order and type of entire functions of several complex variables have been obtained in terms of approximation and interpolation errors